THE ROLE OF SATISFACTION AS MEDIATING FACTOR BETWEEN PERCEIVED SERVICE QUALITY AND LOYALTY - Astrie Arichristyna; Andy Susilo Lukito Budi (Journal of Management and Business, 2012)
This study introduces satisfaction as a mediating factor between perceived service quality and customer loyalty. To confirm its role as a mediator, this study compared results between the no use and the use of satisfaction in a model. This study takes 155 customers of a bakery branch located in Jakarta respondents and this study uses path analysis technique to measure the mediating effect. The result shows that satisfaction mediates nicely to the model and while it plays as a mediating factor, perceived service quality significantly affect to customer loyalty with indirect relationship. The comparison result with the no-use of mediating factor shows that the role of satisfaction as mediating factor increases the power or explanation.